2003
DOI: 10.1097/01.asn.0000069219.88168.39
|View full text |Cite
|
Sign up to set email alerts
|

The Arteriovenous Fistula

Abstract: The ground-breaking article by Brescia and Cimino in 1966 (1) revolutionized the creation of the vascular access, and the Cimino fistula was soon used in almost all dialysis patients. Unfortunately, subsequent wide-spread use of PTFE grafts instead of AV fistulae occurred because of the ease of the surgical technique, the immediate availability of the graft for puncture, the need of high blood flow for high-efficiency, short-duration hemodialysis sessions, and because of financial disincentives against the A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
223
1
22

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 286 publications
(250 citation statements)
references
References 63 publications
4
223
1
22
Order By: Relevance
“…[11], Kumbar, et al [30], Nishitani & Inada [31], and Allon & Robbin [34] also confirmed that blood flow is highly correlated with stenosis and thrombosis issues [12,13,20,28] that alter the frequency spectral characteristics.…”
Section: Blood Flow Sensors Location and Stenotic Severitymentioning
confidence: 92%
See 2 more Smart Citations
“…[11], Kumbar, et al [30], Nishitani & Inada [31], and Allon & Robbin [34] also confirmed that blood flow is highly correlated with stenosis and thrombosis issues [12,13,20,28] that alter the frequency spectral characteristics.…”
Section: Blood Flow Sensors Location and Stenotic Severitymentioning
confidence: 92%
“…Most of the studies demonstrated that significant changes in vascular diameter affect the blood flow-rate [28,29] and change the sound characteristics, which can be identified as higher pitch (frequency) and higher intensity (amplitude) [12,19], and also increase venous pressure [28,30]. A few experimental studies presented different sensor positions or locations for auscultation of the fistula area (arterial and venous side), and showed a limited effect on the sound characteristics.…”
Section: Blood Flow Sensors Location and Stenotic Severitymentioning
confidence: 99%
See 1 more Smart Citation
“…Regular hemodialysis treatments were possible in 1950s through the use of a medical apparatus (Kolff 's twin-coil kidney [14] ), thus projecting the problem of a reliable, capable of repeated use vascular access. Nowadays, the artery-side-to-vein-end-anastomosis has become a standard procedure [15]. In 1952, Aubaniac had described the puncture of the subclavian vein [16].…”
Section: History Of Vascular Accessmentioning
confidence: 99%
“…After anastomosis was performed, the radial artery was ligated distal to the anastomosis, thus resulting in a functional end-to end-anastomosis. Today, the artery-side-to-vein-endanastomosis has become a standard procedure [15]. In 1970, Girardet R. [26] and Brittinger W.D.…”
Section: History Of Vascular Accessmentioning
confidence: 99%